TUTURAN LAKU AMONG DALAM WACANA KELAS - Heri Suwignyo Suwignyo (Fakultas Sastra Universitas Negeri Malang, 2011)
This study aims to describe and explain the laku among utterance in the classs discourse. Laku Among speech act is a natural phenomenon of language use in social and cultural among contexts. To explain the phenomena, ethnographic research was used based on the structure of classroom communication. The result of the study shows that there are three findings of using laku among utterances in the classroom, they are ing ngarsa, ing madya, tut wuri handayani in the initial, middle and final speech acts in the classroom discourse